2010
DOI: 10.1088/0022-3727/43/43/434002
|View full text |Cite
|
Sign up to set email alerts
|

Plasma diagnostics in gas metal arc welding by optical emission spectroscopy

Abstract: The plasma column in the metal inert gas welding process is investigated by optical emission spectroscopy and high-speed imaging. The concentration and repartition of iron vapours are measured and correlated to the plasma and electrode geometric configuration. Plasma temperatures and electron densities were also measured for each studied position in the plasma. The temperatures are calculated using two different methods, allowing validation of the local thermodynamic equilibrium state of the plasma. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 19 publications
1
40
0
3
Order By: Relevance
“…It can be seen that for lower temperatures the arc spreads out less than for higher temperatures like in figure 12a which is in agreement with arcs obtained by relatively low current densities. It should be noted that changing the current density results in a low temperature on the axis of the arc column, which seems to have been observed in the some experimental works that exist in the literature [32,42]. Nevertheless, it is difficult to exactly compare with these experimental data, because they are difficult to perform on the axis due to the passage of liquid metal droplets, and the authors generally dismiss the central zone of the plasma.…”
Section: Arc Column Calculationsmentioning
confidence: 97%
See 3 more Smart Citations
“…It can be seen that for lower temperatures the arc spreads out less than for higher temperatures like in figure 12a which is in agreement with arcs obtained by relatively low current densities. It should be noted that changing the current density results in a low temperature on the axis of the arc column, which seems to have been observed in the some experimental works that exist in the literature [32,42]. Nevertheless, it is difficult to exactly compare with these experimental data, because they are difficult to perform on the axis due to the passage of liquid metal droplets, and the authors generally dismiss the central zone of the plasma.…”
Section: Arc Column Calculationsmentioning
confidence: 97%
“…Gleizes et al [39] showed that metal-vapor contamination to the arc leads to an increase in the energy loss by the radiation, especially at lower temperatures. Zielinska et al [33] and Valensi et al [42] have shown that not only the maximum temperature is less than 15000 K but this maximum temperature is located away from the arc axe as well, which suggest the presence of metal vapors in the plasma particularly near the cathode and the anode regions. a-T = 21000 K under the wire, taken from the literature [24] b-T = 15000 K under the wire, taken from experimental measurements [33,42] Predicted isotherms of a 330 A arc, 10 mm long in argon for this value are shown in Figure 12b.…”
Section: Arc Column Calculationsmentioning
confidence: 97%
See 2 more Smart Citations
“…A number of experimental measurements and calculation models have studied plasma behaviors of in GMAW [9][10][11] . They reported that an arc plasma in GMAW with 100% Ar shielding gas consists of two regions of high-temperature Ar plasma apart from the arc axis and low-temperature Fe plasma near the arc axis.…”
Section: Introductionmentioning
confidence: 99%